Education About the Use of Personal Protective Equipment to Prevent Occupational Accidents Among Vegetable Farmers: Edukasi Penggunaan Alat Pelindung Diri Guna Mencegah Kecelakan Kerja Pada Petani Sayur (JURNAL UNEJ, 2023)
Farmers are one of the jobs with the largest workforce. While working, farmers are at risk of being exposed to occupational accidents ranging from pesticide poisoning, animal bites, sunburn, and accidents caused by work equipment. Based on this, health education through community service is carried out which aims to provide information about various types of occupational accidents and their prevention through the use of personal protective equipment (PPE). This community service was carried out in Wonokitri Village, Tosari District, Pasuruan Regency with 20 vegetable farmers participating. Providing information delivered in lectures and in writing in the form of x-banners and leaflets. Participants played an active role during the implementation of health education, especially discussion sessions. The majority of participants were able to mention the types of occupational accidents and PPE. The implementation of health education needs to be carried out periodically to increase farmers' knowledge regarding occupational health and safety.